Probing superheavy dark matter with gravitational waves - Ligong Bian (SpringerOpen, 2021)
Abstract We study the superheavy dark matter (DM) scenario in an extended B−L model, where one generation of right-handed neutrino ν R is the DM candidate. If there is a new lighter sterile neutrino that co-annihilate with the DM candidate, then the annihilation rate is exponentially enhanced, allowing a DM mass much heavier than the Griest-Kamionkowski bound (∼105 GeV). We demonstrate that a DM mass M νR ≳ 1013 GeV can be achieved. Although beyond the scale of any traditional DM searching strategy, this scenario is testable via gravitational waves (GWs) emitted by the cosmic strings from the U(1) B−L breaking. Quantitative calculations show that the DM mass O $$ \mathcal{O} $$ (109−1013 GeV) can be probed by future GW detectors.